LARVAL CULTURE OF NILE TILAPIA LINEAGES AT DIFFERENT STORAGE DENSITIES - Silva, Emília Tatiane Lopes da (2016)
Larvae from two Nile tilapia (Oreochromis niloticus) lineages were subjected to different storage densities. An experiment was conducted arranged in a 4 x 2 factorial scheme, four storage densities (6.25, 12.50, 18.75 and 25.00 larvae L-1) and two lineages (GIFT and Thai). Larvae from the lineage GIFT and Thai (4,000) were distributed in 32 aquariums with 8 liters of water each, in a randomized order with four replications. The larvae were maintained in the aquariums with constant aeration and natural photoperiod for 36 days. Limnological variables were within the proper range to the specie. Data were subjected to ANOVA, and the Tukey test was used for the density effects. Regarding the biological variables, there was no interaction between lineage and density. The GIFT lineage presented better performance on total length and biomass at the 36th day. Regarding the densities of each lineage, the greater length, weight and weight gain results were found with a density of 6.25 larvae L-1, however, an increase in biomass and a space use optimization occurs using 25 larvae L-1. Therefore, the lineage GIFT at density of 25.00 larvae L-1 is indicated for larval culture.